The death of Alexander the Great - Francois P. Retief; Louise Cilliers (Acta Theologica)
The circumstances of Alexander’s death are reviewed. Since contemporary sources vary in their accounts of the reason for his death, they are briefly reviewed and assessed. The account of Alexander’s final illness is then discussed as recorded in the King’s Journal and the Liber de morte testamentumque Alexandri Magni. The theory that he was poisoned is rejected, as is the hypothesis that he drank himself to death. His final illness shows symptoms characteristic of malignant tertian malaria (Plasmodium falciparum), possibly precipitated by recent wounds, exhaustion and heavy  drinking.